Gender's ontoformativity, or refusing to be spat out of reality: reclaiming queer women's solidarity through experimental writing. (August 2020) - Rudy, Susan
In this article, I argue that queer women – especially cis and trans lesbians – have more in common than contemporary fissures either allow for or acknowledge. Lesbians who recognised their queer sexuality in the 1970s have in common with trans women the shared condition of being, in the words of the 1970s radical feminist Marilyn Frye, 'spat summarily out of reality'. We also share the experience of refusing to accept this condition. I make this argument by manoeuvring away from questions of gender identity and focusing instead on gender's ontoformativity: the astonishing, welcome and transformative fact that new social realities are brought into being by new social practices. I turn to experimental writing to explore this matter. Through this medium, the cis lesbian poet Nicole Brossard and the trans lesbian poet Trace Peterson wrote themselves into worlds, languages and social orders that refused to acknowledge their existence. Brossard was writing in 1970s Montreal, Peterson in early twenty-first-century New York, but what they have in common, indeed what radical lesbian theory from the 1970s shares with contemporary theorising by trans women, is the insight that identifying with men is expected. It is in identifying with women that we are most at risk.